A phase IIA extension study evaluating the effect of booster vaccination with a fractional dose of RTS, S/AS01E in a controlled human malaria infection challenge. Issue 43 (15th October 2021) - Moon, James E.; Greenleaf, Melissa E.; Regules, Jason A.; Debois, Muriel; Duncan, Elizabeth H.; Sedegah, Martha; Chuang, Ilin; Lee, Cynthia K.; Sikaffy, April K.; Garver, Lindsey S.; Ivinson, Karen; Angov, Evelina; et al.
Abstract: Background: We previously demonstrated that RTS, S/AS01B and RTS, S/AS01E vaccination regimens including at least one delayed fractional dose can protect against Plasmodium falciparum malaria in a controlled human malaria infection (CHMI) model, and showed inferiority of a two-dose versus three-dose regimen. In this follow-on trial, we evaluated whether fractional booster vaccination extended or induced protection in previously protected (P-Fx) or non-protected (NP-Fx) participants. Methods: 49 participants (P-Fx: 25; NP-Fx: 24) received a fractional (1/5th dose-volume) RTS, S/AS01E booster 12 months post-primary regimen. They underwent P. falciparum CHMI three weeks later and were then followed for six months for safety and immunogenicity. Results: Overall vaccine efficacy against re-challenge was 53% (95% CI: 37–65%), and similar for P-Fx (52% [95% CI: 28–68%]) and NP-Fx (54% [95% CI: 29–70%]). Efficacy appeared unaffected by primary regimen or previous protection status. Anti-CS (repeat region) antibody geometric mean concentrations (GMCs) increased post-booster vaccination. GMCs were maintained over time in primary three-dose groups but declined in the two-dose group. Protection after re-challenge was associated with higher anti-CS antibody responses. The booster was well-tolerated. Conclusions: A fractional RTS, S/AS01E booster given one year after completion of a primary two- or three-dose RTS, S/AS01 delayed fractional dose regimen can extend or induce protection against CHMI. Clinical Trial Registration: NCT03824236 . linked to this article can be found on the Research Data as well as Figshare https://figshare.com/s/ee025150f9d1ac739361